2004
DOI: 10.1128/iai.72.1.89-93.2004
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Tumor Necrosis Receptor Factor 6/Decoy Receptor 3 Release by Bacterial Antigens in Human Monocytes and Myeloid Dendritic Cells

Abstract: Tumor necrosis factor (TNF) receptor 6 (TR6), also called decoy receptor 3 (DcR3) or M68, is a member of the TNF receptor family that is produced as a secreted protein (3,25,35). Similar to other members of the family, TR6 binds with high affinity to multiple ligands, including Fas ligand (FasL), LIGHT, and TL1A (18,25,35). Since TR6 lacks a transmembrane domain, it can function as an inhibitor by competing with the signal-transducing receptor for the ligand. The recombinant protein was indeed able to inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…The origin of DcR3 in CKD patients is unknown, although studies have suggested that endothelium and bacterial antigen-stimulated immune cells can secrete DcR3 protein (23). In accordance with previous reports, our study confirms that serum concentrations of DcR3 are elevated in patients with CKD compared with those in healthy individuals (12).…”
Section: Discussionsupporting
confidence: 92%
“…The origin of DcR3 in CKD patients is unknown, although studies have suggested that endothelium and bacterial antigen-stimulated immune cells can secrete DcR3 protein (23). In accordance with previous reports, our study confirms that serum concentrations of DcR3 are elevated in patients with CKD compared with those in healthy individuals (12).…”
Section: Discussionsupporting
confidence: 92%
“…Wu et al (8) reported that 56% of tumor patients are serum DcR3 positive, and Ͼ70% of patients with gastric, liver, and gallbladder carcinomas have elevated serum DcR3 levels (Ͼ20 pg/ml). In addition, overexpression of DcR3 has been reported in cases of silicosis or systemic lupus erythematosus (9) as well as in bacterial Ag-stimulated monocytes and myeloid DCs (10). DcR3 can block the effects of its known ligands (FasL, LIGHT, and TL1A) and contributes to tumor growth by impeding the immune response as well as inducing angiogenesis (11).…”
Section: Ecoy Receptor 3 (Dcr3)mentioning
confidence: 99%
“…LIGHT is able to interact with lymphotoxin-h receptor (LThR) to induce cell death (2)(3)(4) or with HVEM to modulate immune cell functions (5-7). Moreover, LIGHT interacts with decoy receptor 3 (8), a soluble receptor overexpressed by tumor cells (9) and activated dendritic cells (10). LIGHT enhances IFN-g secretion by activated T cells (11), and IFN-g potentiates LIGHT-mediated cell death in MDA-MB-231 human breast cancer cells (7,12) as well as in p53-deficient HT-29 human adenocarcinoma cells (13)(14)(15) and Hep3BT2 human hepatoma cells (16,17).…”
Section: Introductionmentioning
confidence: 99%